2022
DOI: 10.3390/ijerph19116907
|View full text |Cite
|
Sign up to set email alerts
|

Infectious Diseases Associated with Desert Dust Outbreaks: A Systematic Review

Abstract: Background: Desert dust outbreaks and dust storms are the major source of particulate matter globally and pose a major threat to human health. We investigated the microorganisms transported with desert dust particles and evaluated their potential impact on human health. Methods: A systematic review of all reports on the association between non-anthropogenic desert dust pollution, dust microorganisms and human health is conducted. Results: In total, 51 articles were included in this review. The affected regions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 69 publications
0
3
0
Order By: Relevance
“…Furthermore, there is evidence that plant, animal, and human pathogens are present in long-distance aeolian transported microbiomes (63,64). These also might be associated with disease outbreaks (65). For instance, a recent study by Björnham et al (64) showed that the foot-and-mouth disease virus could be transmitted over distances of up to 50 km.…”
Section: Airborne Transport Of Microorganismsmentioning
confidence: 99%
“…Furthermore, there is evidence that plant, animal, and human pathogens are present in long-distance aeolian transported microbiomes (63,64). These also might be associated with disease outbreaks (65). For instance, a recent study by Björnham et al (64) showed that the foot-and-mouth disease virus could be transmitted over distances of up to 50 km.…”
Section: Airborne Transport Of Microorganismsmentioning
confidence: 99%
“…Direct and indirect transmission routes of COVID‐19 virus are via touching infected surfaces (skin‐to‐skin, touching infected inanimate objects), then mediating the virus infection through the mouth, nose, or eyes (Moriyama et al., 2020; Peng et al., 2020; Qu et al., 2020). Transmission via inhalation of small, exhaled respiratory air droplets (e.g., close contact within 1m) and aerosols (e.g., presence of microbes and particles <5 μm in diameter that remain in the air for long periods of time and transmitted to others over distances greater than 1 m) is likely effective (Qu et al., 2020; Service, 2020; Vergadi et al., 2022). The most efficient transmission route amid the ongoing pandemic of SARS‐CoV‐2 and its variants is inhalation and exhalation of the viral‐aerosol (Moriyama et al., 2020; Peng et al., 2020; Qu et al., 2020; Service, 2020).…”
Section: Effects On Human Healthmentioning
confidence: 99%
“…Direct and indirect transmission routes of COVID-19 virus are via touching infected surfaces (skin-to-skin, touching infected inanimate objects), then mediating the virus infection through the mouth, nose, or eyes (Moriyama et al, 2020;Peng et al, 2020;Qu et al, 2020). Transmission via inhalation of small, exhaled respiratory air droplets (e.g., close contact within 1m) and aerosols (e.g., presence of microbes and particles <5 μm in diameter that remain in the air for long periods of time and transmitted to others over distances greater than 1 m) is likely effective (Qu et al, 2020;Service, 2020;Vergadi et al, 2022). The most efficient transmission route amid the ongoing pandemic of SARS-CoV-2 and its variants is inhalation and exhalation of the viral-aerosol (Moriyama et al, 2020;Peng et al, 2020;Qu et al, 2020;Service, 2020).…”
Section: Airborne Dust and Covid-19/sars-cov-2mentioning
confidence: 99%